Detection of l-alanylaminopeptidase activity in microorganisms using chromogenic self-immolative enzyme substrates. Issue 10 (15th May 2017) - Cellier, Marie; James, Arthur L.; Orenga, Sylvain; Perry, John D.; Rasul, Ari K.; Stanforth, Stephen P.
Graphical abstract: Abstract: Three potential chromogenic enzymatic probes, each possessing a self-immolative spacer unit, were synthesised for the purpose of detectingl -alanylaminopeptidase activity in microorganisms. An Alizarin-based probe was the most effective, allowing several species to generate strongly coloured colonies in the presence of metal ions.